Accuracy of a low-cost autonomous hexacopter platforms navigation module for a photogrammetric and environmental measurements - Burdziakowski, Paweł; Bobkowska, Katarzyna (International Conference “Environmental Engineering”, 2017)
A photogrammetry and environmental measurements from an unmanned aerial vehicle (UAV) are a low-cost alternative for a traditional aerial photogrammetry. A commercial off-the-shelf products (COTS) offers a variety of cheap components that a suitable to be used on board a UAV. In this paper a low-cost navigation module based on Ublox NEO 8N GPS and Pixhawk flight controller have been described, as a main extrinsic parameters source for aerial photogrammetry, mounted on autonomous hexacopter platform. An accuracy of navigation data logged during the drone flight by a flight controllers navigation module has been compared with geodetic reference measurement. A man controlled flight modes has been tested during a drones loitering above designated point. Due to the situation that, a variety of active electronic, radio transmitters, navigation, inertial and magnetic sensors, are to be placed on a relatively small hexarotor platform with high current power system, overall interference between electronics have to be considered. Paper presents results of navigation module fine tuning process and some technical issues solved during research, that caused an accuracy improvement and interference diminishing. Detailed results are presented and concluded as for the accuracy of navigation based on cheap GPS module is satisfied for execution an autonomous photogrammetry and environmental tasks.